Potato production under zero tillage with rice straw mulching as a promissory technology to diversify rice-based systems in Southwest Coastal Bangladesh - Ramírez, D.; Hossain, M.M.; Rahaman, E.H.M.S.; Mestanza, C.; Rinza, J.; Ninanya, J.; Kreuze, Jan F.; Mendiburu, F. de; Loayza, H.; Gatto, M. (Elsevier, 2025)
Extreme precipitations that promote flooding, salinity, and soils with low drainage and aeration are challenges that affect food production in the Southwest of Bangladesh. After rice cultivation, most lands are kept fallow, emphasizing the urgency of research on techniques that allow crop diversification to guarantee food security. In this study, 2 years-trials on farmers' plots were established in 3 locations of Khulna district-Bangladesh to test potato cultivation under zero tillage with rice straw mulching (ZT) in comparison to conventional cultivation (CT) after rice. A soil quality index (SQI) using the partial least squares method was run considering key soil indicators related to crop production. ZT allowed a higher tuber yield and a lower C footprint than CT. Although neither method significantly affected soil organic carbon stock, there was a significant increment from season 1 to 2 (29.0 ± 11.3 and 45.8 ± 9.4 Mg ha−1, respectively). ZT allowed potato cultivation 15–25 days earlier than CT. Although crop modeling did not show a significant increase in potential tuber yield when simulating the earlier planting of ZT, this advantage will be crucial in the future, considering that high-intensity rainfall events are increasing, flooding the fields and preventing crop cultivation. Alkalinity, carbonates, and anaerobic soil conditions drove the SQI, influencing the elements kept in the past rice cultivation with a concomitant effect in tuber yield. ZT is a promising technology that allows crop diversification based on soil sustainability and labor reduction in challenging agroecologies like Southwest Bangladesh. Socioeconomic studies into adoption and scaling approaches are necessary for a proper technological transfer.